Proposed Digital Marketing Strategy To Improve Operational Performance And Financial Revenue At PT Angkasa Pura I - Aziz Laisa, Abdul; Wandebori, Harimukti (Shofanah Media Berkah, 2024)
PT Angkasa Pura I, a leading airport operator in Indonesia with over 60 years of experience, generates significant revenue of IDR 8.8 trillion annually. However, the company faces challenges in managing diverse customer segments and improving engagement through effective marketing strategies. This study aims to propose a digital marketing strategy to enhance operational performance and financial revenue by optimizing the company's existing resources and leveraging digital platforms. The research employs both internal and external analyses to identify strengths, weaknesses, opportunities, and threats. Internally, PT Angkasa Pura I demonstrates strong human resources and infrastructure capabilities but requires strategic development to strengthen its competitive advantage. Externally, the growth of the transportation and tourism sectors, along with advancements in digital technology, presents significant opportunities. The study highlights threats from competitors offering cost-efficient services, emphasizing the need for differentiation. A proposed digital marketing strategy includes the implementation of Search Engine Optimization (SEO), integrated web services, and collaboration with strategic partners in aviation, tourism, and technology sectors. Enhancing customer satisfaction through operational efficiency and facility quality is also emphasized to build loyalty and trust. The study further suggests strengthening existing marketing programs with innovative, data-driven approaches to attract international customers and business partners. The findings indicate that integrating digital platforms and applying targeted marketing strategies can improve customer experience, operational efficiency, and financial performance. The proposed solutions aim to position PT Angkasa Pura I as a leader in digital transformation within the aviation industry, driving sustainable business growth while meeting customer expectations.